Attitudes about work engagement of different generations—A cross‐sectional study with nurses and supervisors. (17th July 2019) - Huber, Peter; Schubert, Hans‐Joachim
Abstract: Aim: This study investigated whether generation Y nurses (1981–1995) adopt a different attitude about work than generation X caregivers (1966–1980) and baby boomers (1956–1965). Background: Employees' positive attitude to work engagement is a competitive factor for clinics. In age‐diverse team structures, possible different attitudes can lead to conflicts. Methods: As part of a quantitative, descriptive, cross‐sectional study with the survey instrument AVEM‐44, health and nursing staff, as well as nursing directors and ward administrators, were interviewed. Results: A total of N  = 992 individuals ( n  = 312 nursing directors, n  = 259 ward administrators and n  = 421 nurses) were included in the study. Nurses and executives viewed generation Y as being less willing to give oneself out and as attaching less importance to work than generation X and the baby boomers. On the other hand, professional ambition was more important to generation Y than the older generations. Conclusions: Transformational leadership behaviour represents an approach to guide employees of different generations individually and to harmonize different attitudes. Implications for Nurse Management: To lead employees transformationally, it is necessary to know generation‐specific differences concerning attitudes towards work.